What Can Gamma Delta T Cells Contribute to an HIV Cure? - Juno, Jennifer A.; Kent, Stephen J. (Frontiers in Cellular and Infection Microbiology, 2020)
Elimination of the latent HIV reservoir remains a major barrier to achieving an HIV cure. In this review, we discuss the cytolytic nature of human gamma delta T cells and highlight the emerging evidence that they can target and eliminate HIV-infected T cells. Based on observations from human clinical trials assessing gamma delta immunotherapy in oncology, we suggest key questions and research priorities for the study of these unique T cells in HIV cure research.